Echte venten: een verkennend onderzoek naar mannelijkheid bij Limburgse mijnwerkers - Delbroek, Bart; Roels, Leen (Studies over de sociaaleconomische geschiedenis van Limburg, 2018)
Real men: an exploratory research into masculinity among Belgian-Limburg minersIn this article we want to initiate a gender approach in the study of the labour market for miners in Limburg, in particular by looking at the ways in which miners defined and expressed their masculinity. Interviews, testimonies and a number of contemporary sources show that miners in the Belgian Limburg mines defined and expressed their masculinity by working hard, being competitive, having lots of after-work activities, not showing fear and minimizing risks. The gender identity among miners in the Campine area arose partly as a result of broader socio-economic evolutions: underground women’s work was banned in Belgium since 1911, which made the underground the exclusive terrain of men. Another decisive factor was the drastically new labour organization that was introduced by the Limburg mining companies. The traditional miners’ occupation lost much of its charm through mechanization and stricter supervision. Professional knowledge and autonomy were (partly) replaced by physical strength and competitiveness. This analysis shows that employers also used a certain form of hegemonic masculinity strategically.